Arkivets pleroma - Andreasen, Torsten (K&K - Kultur og Klasse, 2016)
In 1956, on a commission from the French Ministry of Foreign Affairs, Alain Resnais made a short film about the French national library called Toute la mémoire du monde. The film performs a vertical movement from indiscernible form and prevalent darkness upon the face of the deep in the library cellars to the summits of institutional power in its domed view of the well-ordered rows of tables and chairs in the Labrouste reading room. This vertical axis is established and maintained by the horizontal library operations that promise to transform the library objects from chaotic heap to collective happiness, or what this article has called the promised movement from plethora to pleroma. Resnais’ film intervenes in an ongoing discourse about the possibility of archival pleroma, thinking machines and the possible beneficial consequences for human existence. But the question is whether such persistent happy belief in the fall of the very last practical obstacles for pleroma does not overlook the view from Resnais’ domed shot: The view indicating that sinister fantasies of the pleroma of knowledge persist in relation to fantasies of political organisation and that the guardians of the archive will always patrol the aisles of the reading room.